Biomarkers in cancer immunotherapy - Schumacher, Ton N; Kesmir, Can; van Buuren, Marit M (Cancer cell, 2015)
Antibodies against T cell checkpoint molecules have started to revolutionize cancer treatment. Nevertheless, less than half of all patients respond to these immunotherapies. Recent work supports the potential value of biomarkers that predict therapy outcome and inspires the development of assay systems that interrogate other aspects of the cancer-immunity cycle.